(untitled) (Bangladesh Veterinarian, 2022)
The prevalence of snail-borne trematodes (SBTs) of cattle and their vector snails in Rajshahi district in Bangladesh were determined. A total of 380 faecal samples of cattle were collected and examined using Modified Stoll’s Ova Counting Technique. Of the smaples examined, 130 (34.2%) animals were found affected with SBTs, and the mean egg per gram of faeces (EPG) was 180.3 ± 0.8. The trematodal infections by Fasciola gigantica (1.1%), different amphistomes (32.9%), and Schistosoma spindale (0.8%) were detected among the infected cattle. The effects of age, sex, breed, and body condition of the cattle on the prevalence of SBTs were determined. The infection rate was higher in young (> 2- 4 years) cattle (46.5%), followed by calves of ≤ 2 years (35.3%), and the lowest in older (> 4 years) cattle (20%). The prevalence of trematode infections was significantly (P<0.0001) higher in females (36.5%) than in male (28.3%) cattle. The prevalence was higher in cattle with poor body condition (48.7%) than in cattle with normal body condition (24.8%). Significantly (P<0.008) higher prevalence of trematode infection was recorded in indigenous cattle (41.2%) than in cross-bred cattle (26.9%). It is suggested that SBT infection is a common problem in cattle in Rajshahi district of Bangladesh. Particular emphasis should be given to proper management and regular deworming, and sustainable control measures should be developed for the prevention of SBT infection in cattle. Bangl. vet. 2021. Vol. 38, No. 1-2, 24–32